Die Mosaiken der Acheiropoietos-Basilika in Thessaloniki Eine vergleichende Analyse dekorativer Mosaiken des 5. und 6. Jahrhunderts - Fourlas, Benjamin (Millennium-Studien / Millennium Studies, 2012)
The volume examinesfurther questions on the early Byzantine mosaics in the metropolis, and in particular their problematic chronology. A number of mosaics from the entire Mediterranean, which have to date received little attention, are also taken into account.